A Study on Graph Theory and Its Applications: Exploring the Relevance and Applications of Graph Theory (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As Graph theory becomes implemented in many fields of mathematics, science and technology, it becomes more and more relevant. This is widely used in a number of areas such as biochemistry, electric engineering, informatics and work on operations. Throughout other fields of mathematics pure fundamental findings were often demonstrated by strong combinational methods used in graph theory.